Patients using new oral anticoagulants - results of an epidemiological study - Zatloukalová, Anna; Janoutová, Jana; Homza, Miroslav; Machazcka, Ondřej; Janout, Vladimír (Profese Online, 2018)
Background: New oral anticoagulants are undoubtedly a big step forward. Their use is safer than warfarin, and there is no need for monitoring, which provides a great deal of relief especially for less-moving patients. In spite of their great advantages, especially for the optimization of treatment, the group of patients and their basics should be monitored.Aim: The aim of the study was to find out the basic characteristics of patients, including comorbidities and other important parameters.Methods: The data was obtained from the Benedor cardiac database in Ostrava. The selection criterion was the use of DOACs (Direct Oral Anticoagulants), i.e. the use of dabigatran, rivaroxaban or apixaban. The EpiData program was used for data processing. Data was also exported and processed in Excel, Stata and OpenEpi. The total number of respondents was 334 patients.Results: The most prominent feature of patients was overweight and obese 55.8%. Normal weight was maintained by only 11.3% of patients. Most patients suffered from three other diseases (most often hypertension and ischemic heart disease).Conclusion: In general, a group of patients may be characterized as polymorbid, overweight or obese. It would be appropriate to lead patients to a healthy lifestyle and thus improve their health.
Keywords: New peroral anticoagulants; dabigatran; rivaroxaban; apixaban; darexaban